A symptom diary to assess severe premenstrual syndrome and premenstrual dysphoric disorder - Janda, Carolyn; Kues, Johanna N.; Andersson, Gerhard; Kleinstäuber, Maria; Weise, Cornelia (Women & Health, 2017)
The differentiation between premenstrual syndrome (PMS) and premenstrual dysphoric disorder (PMDD) has been widely discussed. PMDD is listed as a mental disorder in the DSM-5, whereas PMS is not considered as a mental disorder in any diagnostic manual. Consequently, PMS is operationalized in different ways. Keeping a symptom diary is required to diagnose PMDD but is also recommended for PMS. The aim of our study was, therefore, to operationalize PMS and PMDD within a DSM-5-based symptom diary. We developed a symptom-intensity-score (SI-score) and an interference-score (INT-score) to evaluate the symptom diary. Ninety-eight women (aged 20–45 years) completed a symptom diary over two menstrual cycles, a retrospective screening for premenstrual symptoms, and answered additional impairment questionnaires from August 2013 to August 2015. The scores revealed moderate to good reliability (Cronbach’s α = 0.83–0.96). Convergent validity was shown by significant correlations with a retrospective screening, the Pain Disability Index, and the German PMS-Impact Questionnaire. Discriminant validity was indicated by low correlations with the Big Five Inventory-10. These scores may facilitate the evaluation of prospective symptom ratings in research and clinical practice. Future research should focus on continuing to validate the scores (e.g., in an ambulatory setting).
CRIS-Team Scopus Importer:2024-03-27
Keywords: DSM-5; menstrual cycle; premenstrual dysphoric disorder (PMDD); premenstrual syndrome (PMS); psychological diagnostics; symptom diary